Diffuse maculopapular exanthema and a positive lymphocyte transformation test reaction in response to clarithromycin. Issue 9 (25th August 2018) - Ito, Toshiki
Abstract: Macrolides are one of the most widely used antibiotics, but the mechanisms underlying macrolide allergy have not been clearly elucidated. Diffuse maculopapular exanthema caused by clarithromycin is extremely rare, of which clinical images have not been reported. Here, we report a case of a 55-year-old Japanese female who was treated with oral clarithromycin and lysozyme hydrochloride due to odontogenic maxillary sinusitis. On the 15th day after starting both drugs, she suffered from diffuse maculopapular exanthema, which worsened despite the discontinuation of lysozyme hydrochloride and the introduction of treatment with oral and topical corticosteroids and oral levocetirizine. Clarithromycin was discontinued and an intravenous corticosteroid introduced on the 19th day. A lymphocyte transformation test was positive for clarithromycin but negative for lysozyme hydrochloride. Although adverse effects of clarithromycin are extremely rare, physicians should be aware of clarithromycin as a potential cause of a type IV allergic reaction.